MANAJEMEN STRATEGIK MUTU REKRUTMEN TENAGA KEPENDIDIKAN DI INSTITUT AGAMA ISLAM NEGERI MADURA - Robby Arini; Achmad Muhlis (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2020)
This article describes the implementation of quality management strategic recruitment of education personnel in the state islamic institute of madura. State islamic institute of madura as one of the earliest educational institutes which was present based on the background of the community's need for higher education and then the results will be returned to the community. so as to ensuring the quality of graduates it is necessary to recruit the quality of education personnel so that ensuring the expected educational success.strategic management of the recruitments quality of education personnel in the state islamic institute of madura so far is good enough, although there are some things that need to improved with the form of recruitment strategic management of education personnel in the state islamic institute of madura is good enought. It can be seen from several things, namely : quality of recruitment, source of recruitment. Than for the implementation of recruitment strategic management of the quality education personnel in the state islamic institute of madura more on : human resources seen in recruitment and constraints in recruitment